Vanishing Vienna: modernism, philosemitism, and Jews in a postwar city - Tanzer, Frances (Jewish culture and contexts, 2024)
"This book reveals the foundational role philosemitism played in the effort to reimagine urban cultures after the Holocaust. This book uncovers a seldom discussed aspect of the postwar era-a society that continues to consume, redefine, and bestow symbolic meaning on the victims in their relative absence"--